Retroperitoneal Schwannoma: A Case Report and Review of the Literature (Journal of Bangladesh College of Physicians and Surgeons, 2016)
A 45 years old woman admitted to our Hospital with pain in the right flank and right hypochondrium. Her abdominal USG and CT scan showed a large complex cystic mass present in the deep soft tissue compressing the right kidney. Multiple gall bladder stones were also found in imaging. Both the adrenal glands and left kidney had a normal appearance. The mass was completely resected with extended right subcostal incision along with excision of Gall bladder. Histopathological examination of the specimen revealed a degenerated schwannoma. Patient was discharged on 8th day after operation without any complications.J Bangladesh Coll Phys Surg 2015; 33(4): 225-228